The COVID-19 pandemic and a new public health problem: The emotional impacts on health professionals (Research, Society and Development, 2021)
The present work aims to reflect on the mental health of professionals working in the front line and, with this, to raise discussions about the emotional impacts on their lives and on society as a result of the COVID-19 pandemic. The study comprises an integrative literature review. Searches for publications were carried out in four bibliographic databases - PubMed, Virtual Health Library (VHL), Scientific Electronic Library Online (SciELO) and Latin American and Caribbean Literature in Health Sciences (LILACS). 16 articles published between the years 2019 to 2021 were selected, written in English, Portuguese or Spanish as a source of studies and for addressing the guiding question of the review. Research has shown the emergence of a vicious circle in which, with the stress of the current scenario, the population disregards the isolation measures adopted, resulting in an increase in the number of cases and overcrowding in hospitals. With this, there is a physical and emotional burden on health professionals who face the daily fight against the virus.